Bank Mergers and Acquisitions in Emerging Markets: Evidence from Asia and Latin America - Tim Zhou (European Journal of Finance, 2011)
Following a global wave of consolidation in the banking industry, this study analyses 132 mergers and acquisitions (M&As) involving banks in emerging markets in Asia and Latin America between 1998 and 2009. An event study measures the change in shareholder value for acquirers and targets; and a multivariate regression identifies the drivers of the change in shareholder value for acquirers. On average M&A creates shareholder value for target firms, while acquirer firms do not lose shareholder value. Geographical diversification creates shareholder value for acquirers. Acquirer shareholders benefit from the acquisition of underperforming targets; from transactions settled by cash rather than exchange of equity; and from government-instigated M&A transactions.